Absorption effects on plasmon polariton-gap solitons in Kerr/metamaterial superlattices (2014)
ABSTRACT: A thorough study of the absorption effects on the plasmon polariton-gap solitoninduced transparency in 1D Kerr/metamaterial superlattices is presented. Results indicate that for frequencies close to the bottom or top edge of the bulk-like longitudinal plasmon-polariton gap, the transmission of a finite Kerr/metamaterial superlattice presents a multistable behavior, switching from very low values to the maximum transparency at particular values of the incident power even in the presence of loss effects. Moreover, calculations suggest the existence of resonant plasmon polariton-gap solitons of various orders depending on the particular value of the incident power. The present results reveal that plasmon polariton-gap soliton-induced resonant solutions lead to the transparency of a stack with nonlinear inclusions, a nonlinear optical analog of the electronic barrier-transmission resonances.